Had A Role Of Polri An Implementing Crimes Violent (Study In Subdit Iii Jahtanras Directorate Of General Criminal Reservations Polda North Sumatera) - Jona Wira Karya; T Riza Zarzani; Ismaidar (LEGAL BRIEF, 2022)
Various factors, such as low education, religious morals, and environmental factors, can lead to a criminal act. However, the factors that significantly influence the emergence of criminal acts are economic factors. Economic needs must be met urgently. At the same time, the available job opportunities cannot meet all Indonesian people to work and earn a steady income, so that in meeting their needs, many people do everything they can to meet their needs. Accompanied by” or “followed by” violence or threats of violence must be closely related to efforts to facilitate or prepare or, if caught red-handed, to allow escape for oneself. This study aims to find out how to analyze the legal arrangements for violent crimes, analyze the factors that cause violent crimes, and explore the efforts of the Police Sub-Directorate III of Jahtanras General Criminal Investigation of the North Sumatra Police in Overcoming the Level of Violent Crime. It is an Empirical juridical with data collection tools at the location of the Police Sub Directorate III Jahtanras General criminal investigation of the North Sumatra Police related to the problem of this thesis. Based on the research results obtained, Crime in the Criminal Code is divided into two, namely Crime and Violations. The division is based on a principal difference, namely the division of Crime is arranged in Book II of the Criminal Code, in the Criminal Code Crimes Against Property, for example, theft in Article 362 up to 367 of the Criminal Code, Extortion in Articles 368 to 371 of the Criminal Code, Fraud in Articles 406 to 412 of the Criminal Code. According to the law, theft is divided into five types, namely common theft, regulated in Article 362 of the Criminal Code, theft with aggravation is regulated in Article 363 of the Criminal Code, theft with violence is regulated in Article 365 of the Criminal Code, theft within the family is regulated in Article 367 of the Criminal Code, Crimes Against A Person's Body and Life such as Persecution and Murder.